HAMBATAN – HAMBATAN DALAM UPAYA PENGEMBANGAN USAHA KECIL DAN MENENGAH (UKM) DENGAN MENGGUNAKAN TEKNOLOGI INFORMASI ( E-COMMERCE ) UNTUK MENINGKATKAN PENJUALAN BIBIT IKAN DI DESA PLOSOBUDEN KEC.DEKET KAB. LAMONGAN - Danu Kusbandono; Sabilar Rosyad (STIE Mahardhika, 2020)
This research focuses the problems on how the business barrier analysis that uses e-commerce for sellers of fish seedlings in the village Buden. The theory used in this study is the Uses and Gratifications theory. Methods of research using qualitative research methods. For retrieval information and data set set 5 informant. The data collection techniques used in this research are structured interviews directly. The results of the study found that fundamental issues were delays in shipping products from sellers. Solution: buyer declares estimated delivery time as well as possible delay in delivery. Item issues do not match buyer expectations. Solution: Photo Promotion of a product, especially fish seed products, it is better to use fish type, packaging, and delivery as promotional photo, because it is more realistic than promotional photos that do not use models. Delivery problems do not match the buyer's address. WORKAROUND: If someone wants to buy an item online, he should learn the full address of the delivery destination first, to avoid sending errors by the buyer. Fraud or item issues are not delivered. Solution: Learn about sales performance online through customer responses usually listed on the online Seller promotion page. Information on the response can be used by online sellers to create a reference to sales and service performance, as much as possible the response was publicly exposed on the seller's website. With the buyer's response, it can indirectly provide information on the reputation of online sellers. The suggestion or feedback in this research is: This research still needs to be done development, therefore for future research on e-commerce need to be studied more about analysis of barriers online business using Website or online store. Then for business people sales of fish seedlings in the village Buden, can examine the results of this research as an alternative learning solution for the improvement of online business, either as a seller, reseller, or buyer.